ATN incorporating cerebrospinal fluid neurofilament light chain detects frontotemporal lobar degeneration. Issue 5 (23rd November 2020) - Cousins, Katheryn A.Q.; Phillips, Jeffrey S.; Irwin, David J.; Lee, Edward B.; Wolk, David A.; Shaw, Leslie M.; Zetterberg, Henrik; Blennow, Kaj; Burke, Sarah E.; Kinney, Nikolas G.; Gibbons, Garrett S.; McMillan, Corey T.; et al.
Abstract: Introduction: The ATN framework provides an in vivo diagnosis of Alzheimer's disease (AD) using cerebrospinal fluid (CSF) biomarkers of pathologic amyloid plaques (A), tangles (T), and neurodegeneration (N). ATN is rarely evaluated in pathologically confirmed patients and its poor sensitivity to suspected non‐Alzheimer's pathophysiologies (SNAP), including frontotemporal lobar degeneration (FTLD), leads to misdiagnoses. We compared accuracy of ATN (ATNTAU ) using CSF total tau (t‐tau) to a modified strategy (ATNNfL ) using CSF neurofilament light chain (NfL) in an autopsy cohort. Methods: ATNTAU and ATNNfL were trained in an independent sample and validated in autopsy‐confirmed AD (n = 67) and FTLD (n = 27). Results: ATNNfL more accurately identified FTLD as SNAP (sensitivity = 0.93, specificity = 0.94) than ATNTAU (sensitivity = 0.44, specificity = 0.97), even in cases with co‐occurring AD and FTLD. ATNNfL misclassified fewer AD and FTLD as "Normal" (2%) than ATNTAU (14%). Discussion: ATNNfL is a promising diagnostic strategy that may accurately identify both AD and FTLD, even when pathologies co‐occur.